Adaptive Noise Cancellation System for Low Frequency Transmission of Sound in Open Fan Aircraft - Steven Griffin; Adam Weston; Jeff Anderson (Shock and Vibration)
This paper describes the use of a structural/acoustic model of a section of a large aircraft to help define the sensor/actuator architecture that was used in a hardware demonstration of adaptive noise cancellation. Disturbances considered were representative of propeller-induced disturbances from an open fan aircraft. Controller on and controller off results from a hardware demonstration on a portion of a large aircraft are also included. The use of the model has facilitated the development of a new testing technique, closely related to modal testing, that can be used to find good structural actuator locations for adaptive noise cancellation.